Circulating miRNAs in hand osteoarthritis. Issue 2 (February 2023) - Baloun, J.; Pekáčová, A.; Švec, X.; Kropáčková, T.; Horvathová, V.; Hulejová, H.; Prajzlerová, K.; Růžičková, O.; Šléglová, O.; Gatterová, J.; Tomčík, M.; Filková, M.; et al.
Summary: Objective: Hand osteoarthritis (OA) is a frequent musculoskeletal disorder with an increasing prevalence during ageing. This study aimed to evaluate circulating microRNAs (miRNAs) in the plasma of patients with hand OA compared with age- and sex-matched healthy control subjects. Methods: In total, 238 participants (96 with erosive and 73 with non-erosive hand OA patients and 69 healthy control subjects) were included in this study. All patients underwent clinical examinations, including self-reported measures (AUSCAN and Algofunctional index). Radiographs of both hands were scored with the Kallman scale. The profile of miRNAs in plasma was screened using TaqMan™ Low-Density Array, and candidate miRNAs were validated on two quantitative real-time PCR (qRT-PCR) systems (QuantStudio and SmartChip). Results: Of all the 754 miRNAs, 40 miRNAs were different between hand OA patients and healthy control subjects in the screening cohort. Following the two-phase validation process, three miRNAs (miR-23a-3p, miR-146a-5p, and miR-652-3p) were increased in patients with hand OA compared with healthy control subjects and were associated with the AUSCAN sum score and AUSCAN pain. Furthermore, an inverse correlation of miR-222-3p with the Kallman radiographic score was found. The expression of miRNAs did not differ between erosive and non-erosive hand OA. Conclusion: The profile of circulating miRNAs could unveil candidate biomarkers associated with hand OA symptoms. Longitudinal studies are required to determine the role of miRNAs in hand OA.